Nanomaterials and immune checkpoint inhibitors in cancer immunotherapy: the synergistic innovation prospects - Chen, Jing; Cheng, Xue (Frontiers in Immunology, 2025)
Tumor cells can utilize the immune checkpoint pathway to inhibit T cell activation and evade the attack of tumor specific T cells. While immune checkpoint inhibitors (ICIs) competitively bind to checkpoint molecules to block checkpoint mediated suppression of the immune system. Immune checkpoint inhibitors have emerged as a milestone in cancer immunotherapy, demonstrating significant efficacy in various cancers. However, their clinical application still faces challenges such as low response rates (<30% in solid tumors), significant side effects, and suppression by the tumor microenvironment. Nanomaterials offer new solutions to optimize the therapeutic effects of ICIs. This article explores the potential of combining nanomaterials with ICIs in cancer treatment.